A Proteomic View of the Cross-Talk Between Early Intestinal Microbiota and Poultry Immune System - Rodrigues, D. R.; Wilson, K. M.; Trombetta, M.; Briggs, W. N.; Duff, A. F.; Chasser, K. M.; Bottje, W. G.; Bielke, L. (Frontiers in Physiology, 2020)
Proteomics has been used for investigating cross-talk between the intestinal microbiome and host biological processes. In this study, an in ovo technique and proteomics approach was used to address how early bacterial colonization in the gastrointestinal tract (GIT) could modulate inflammatory and immune responses in young broilers. Embryos at 18 embryogenic days were inoculated with saline (S), 102 CFU of Citrobacter freundii (CF), Citrobacter species (C2), or lactic acid bacteria (L) into the amnion. At 10 d post-hatch, ileum samples from 12 birds per treatment were selected for tandem mass spectrometry analysis. Our further findings indicated that treatment-specific influences on early GIT microbiota resulted in different immune responses in mature broilers. Predicted functional analyses revealed activation of inflammation pathways in broilers treated in ovo with L and CF. Exposure to L enhanced functional annotation related to activation, trafficking of immune cells, and skeletal growth based-network, while CF inhibited biological functions associated with immune cell migration and inflammatory response. These results highlighted that proper immune function was dependent on specific GIT microbiota profiles, in which early-life exposure to L-based probiotic may have modulated the immune functions, whereas neonatal colonization of Enterobacteriaceae strains may have led to immune dysregulation associated with chronic inflammation.